ACUTE TOXICITY OF OPUNTIA FICUS INDICA AND PISTACIA LENTISCUS SEED OILS IN MICE - BOUKELOUA, AHMED; BELKHIRI, ABDELMALIK; DJERROU, Zouhir; BAHRI, Laid; BOULEBDA, Nadji; Hamdi Pacha, Youcef (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Opuntia ficus indica and Pistacia lentiscus L. seeds are used in traditional medicine. The objective of this study was to investigate the toxicity of the fixed oil of Opuntia ficus indica and Pistacia lentiscus L. seeds in mice through determination of LD50 values, and also the physicochemical characteristics of the fixed oil of these oils. The acute toxicity of their fixed oil were also investigated in mice using the method of Kabba and Berhens. The fixed oil of Pistacia lentiscus and Opuntia ficus indica seeds were extracted and analyzed for its chemical and physical properties such as acid value, free fatty acid percentage (% FFA), iodine index, and saponification value as well as refractive index and density. LD50 values obtained by single doses, orally and intraperitoneally administered in mice, were respectively 43 ± 0,8 ;[40.7- 45.4 ] ml/kg body wt. p.o. and 2.72 ± 0,1 ;[2.52–2.92] ml/kg body wt. i.p. for Opuntia ficus indica ; and 37 ± 1 ;[34.4 – 39.8 ] ml/kg body wt. p.o. and 2.52 ± 0,2 ;[2.22 – 2.81 ] ml/kg body wt. i.p. for Pistacia lentiscus respectively. The yields of seed oil were respectively calculated as 20.25% and 10.41%. The acid and free fatty acid values indicated that the oil has a low acidity